Late-onset fabry disease presenting with unexplained renal failure, left ventricular hypertrophy, and recurrent syncope: a case report - Qisu Ying; Xiu Yang; Ning Zhao; Ming Wang; Yu Wu; Xuexue Shi; Jie Shen; Min Zhao; Wenjun Wang; Yingying Qian; Qi Chen; Yong Mao (Orphanet Journal of Rare Diseases)
Abstract Late-onset cardiac manifestations of Fabry disease are frequently associated with high rates of missed diagnoses and misdiagnoses. We present a case of a 71-year-old male with late-onset Fabry disease whose diagnosis was delayed due to the absence of typical symptoms. The patient has a history of nephrotic syndrome and is currently suffering from end-stage renal disease (ESRD), undergoing maintenance hemodialysis. He was previously diagnosed with diffuse left ventricular hypertrophy and heart block. Upon admission, cardiac examination revealed reduced longitudinal strain of the left ventricle. Fabry disease was suspected due to recurrent heart failure, persistent slight elevation in troponin I (TNI) levels, recurrent syncope, and hearing loss. Subsequent measurement of α-galactosidase A activity and genetic testing confirmed the diagnosis. This case highlights the importance of considering Fabry disease in patients with renal failure, recurrent heart failure, persistent slight elevation in TNI levels, and bilateral interventricular septum syndrome.